Ethical Duties of an Advocate Representing a Client in Mediation (Comparative Legal Analysis of Georgian and American Models) - Chantladze, Rati (Alternative Dispute Resolution Yearbook, 2019)
Mediation as a means of alternative dispute resolution is recognized by western legal systems. It has developed at an exceptionally fast pace in the United States of America, which, of course, was accompanied by discussions and reasoning in literature accumulating valuable knowledge and experience that undoubtedly must interest lawyer and non-lawyer specialists working in the field of mediation. Creation of a legislative base necessary for the development of the field of mediation in Georgia is underway. After the adoption of amendments to the procedural legislation, the parliament of Georgia admitted for discussion a draft law on mediation, which will be voted on in near future. The participants of a mediation process have a special status, role and function, which they must carry out in order for mediation to be successful. A special role and function is borne by the advocate representing a party, who much like in case of court or arbitration proceedings, seeks to achieve the best possible outcome for the party; however, as opposed to a classical dispute, advocates engage in communication of a different nature with the participants of the mediation process and do not act within the scope of the predetermined procedural restrictions. The representative powers of advocates are by no means unrestricted and they may be held liable for various breaches of law. The present article identifies and analyzes such provisions with the aim of their further improvement and development, and includes recommendations.